Issues in liquidity management in banking system: An empirical evidence from Indian commercial banks - Raavinuthala Satya Krishna Sharma; Kumar Bijoy; Arunaditya Sahay (Cogent Economics & Finance)
Maintaining the optimal level of liquidity in the banking system has always been a challenge for banks globally. Liquidity deficit Indian Banks turned to liquidity surplus due to the demonetization of higher denomination currencies in November 2016. The liquidity deficit has the potential to trigger systemic risk whereas a surplus can weaken monetary transmission leading to the creation of asset bubbles. This study explores the impact of various interventions of policymakers to maintain the optimal liquidity by simultaneously insulating the banks’ profitability and overall economic growth from the policy’s negative impact using Auto-Regressive Distributed Lag (ARDL) regression. The study records and analyses the impacts of “Fiscal Deficit”, “Lending and Deposit Rates”, and “Credit Growth Rate” on Liquidity Deficit, GDP growth and Banks’ Profitability levels. It is found that Fiscal deficit is negatively related to Liquidity deficit and GDP growth but increases Banks’ profit whereas Lending rates have an insignificant impact on Liquidity Deficit. Increasing Deposit rates have a positive impact on Liquidity deficit, negative on Banks’ Profit, and immediate positive relationships with GDP growth which changes to negative at the third lag. Similarly, the Credit growth rate has a positive relationship with the Liquidity deficit, augments GDP growth, and reduces Banks’ profit. It is also observed that the profit of Indian Scheduled Commercial banks has reduced after the demonetization. This study, apart from contributing to academic literature, will help the monetary authorities and the financial institutions in their policy decisions for managing the liquidity issues in the market.